Advancing Nanomedicine Through Electron Microscopy: Insights Into Nanoparticle Cellular Interactions and Biomedical Applications - Akhtar S; Zuhair F (International Journal of Nanomedicine)
Sultan Akhtar,1 Fatimah Zuhair2 1Department of Biophysics Research, Institute for Research and Medical Consultations (IRMC), Imam Abdulrahman Bin Faisal University, Dammam, 31441, Saudi Arabia; 2Department of Infection Control, Alzahra General Hospital, Qatif, 31911, Saudi ArabiaCorrespondence: Sultan Akhtar, Department of Biophysics Research, Institute for Research and Medical Consultations (IRMC), Imam Abdulrahman Bin Faisal University, Dammam, 31441, Saudi Arabia, Tel +966133330876, Email suakhtar@iau.edu.saAbstract: Nanomedicine has revolutionized cancer treatment by the development of nanoparticles (NPs) that offer targeted therapeutic delivery and reduced side effects. NPs research in nanomedicine significantly focuses on understanding their cellular interactions and intracellular mechanisms. A precise understanding of nanoparticle interactions at the subcellular level is crucial for their effective application in cancer therapy. Electron microscopy has proven essential, offering high-resolution insights into nanoparticle behavior within biological systems. This article reviews the role of electron microscopy in elucidating the cellular uptake and intracellular interactions of NPs. Transmission electron microscopy (TEM) provides imaging capabilities, such as cryo three-dimensional tomography, which offer in-depth insights into nanoparticle localization, endocytosis pathways, and subcellular interactions, while high resolution-TEM is primarily used for studying the atomic structure of isolated NPs rather than nanoparticles within cells or tissues. On the other hand, scanning electron microscopy (SEM) is ideal for examining larger surface areas and provides a broader perspective on the morphology and topography of the samples. The review highlights the advantages of electron microscopy in visualizing nanoparticle interactions with cellular structures and tracking their mechanisms of action. It also addresses the challenges associated with electron microscopy characterization, such as tedious sample preparation, static imaging limitations, and a restricted field of view. By examining various nanoparticle uptake pathways, and cellular destination of NPs with examples, the article emphasizes the importance of these pathways to optimize nanoparticle design and enhance therapeutic efficacy. This review underscores the need for continued advancement in electron microscopy techniques to improve the effectiveness of nanomedicine and address existing challenges. In summary, electron microscopy is a key tool for advancing our understanding of nanoparticle behavior in biological contexts, aiding in the design and optimization of nanomedicines by providing insights into nanoparticle cellular dynamics, uptake mechanisms, and therapeutic applications.Plain Language Summary: Cancer remains one of the leading causes of death worldwide, with incidence and mortality rates projected to rise significantly in the coming years. In recent years, tiny-objects known as nanoparticles are widely utilized in therapeutic applications to improve treatment outcomes and effectiveness in combating cancer. This article explores how electron microscopy is transforming cancer treatment using nanoparticles. Nanoparticles are designed to deliver drugs directly to cancer cells, improving treatment options while reducing side effects. A detailed information is crucial in order to understand how these nanoparticles interact with cells. Electron microscopy techniques such as transmission electron microscopy and scanning electron microscopy play a key role in obtaining such information. Electron microscopes enables scientists to visualize nanoparticles and cells with enhanced clarity and magnification. This capability is helping to understand how nanoparticles enter the cells, transport in specific locations, and interact with various cellular components. Moreover, it allows the examination of the larger surface areas of the treated cells, revealing the overall morphology and topography of the nanoparticles and their interactions with cell structures.The objective of this study is to investigate the role of electron microscopy in understanding the cellular uptake, intracellular interactions, and subcellular localization of nanoparticles used in cancer nanomedicine. It aims to highlight how advanced electron microscopy techniques like transmission electron microscopy and scanning electron microscopy provide critical insights into nanoparticle behavior within biological systems, while addressing challenges such as sample preparation and imaging limitations. The study underscores the need for continued innovation in electron microscopy technologies to optimize nanoparticle-based therapeutic design and improve cancer treatment outcomes.This review outlines studies evaluating the use of electron microscopy techniques in nanoparticle applications for cancer research, highlighting their advantages and limitations. It focuses on nanoparticle uptake pathways, cellular destinations, and recent examples of nanoparticle interactions with cancer cells. Electron microscopy, particularly transmission electron microscopy, plays a vital role in visualizing nanoparticle behavior within cells, revealing ultrastructural changes such as nanoparticle aggregation, shape, and interactions with cellular membranes and organelles. Transmission electron microscopy offers precise insights into nanoparticle uptake, transport, and exit, while three-dimensional (3D) tomography provides detailed reconstructions of nanoparticle localization. However, challenges like sample preparation and artifacts persist, with rapid freezing methods, such as plunge-freezing particularly, high-pressure freezing, proving effective in preserving native cellular structures. Combining electron microscopy with techniques like flow cytometry improves the study of nanoparticle interactions by offering both ultrastructural and quantitative data, enabling accurate analysis of nanoparticle uptake and behavior in cancer cells. Keywords: cancer cells, ultrastructural analysis, uptake pathways, challenges, nanomedicine